2016
DOI: 10.1002/2016ja022644
|View full text |Cite
|
Sign up to set email alerts
|

Pressure and ion composition boundaries at Mars

Abstract: This study analyzes results from a multifluid MHD simulation to investigate the shape and structure of the pressure and composition boundaries at Mars, which can provide physical insight for the observational analysis. These boundaries are examined via the unity contours and gradients of the plasma β, as well as β∗, which includes the dynamic pressure in the numerator, and the ion mass and number density ratios. It is found that unity contours are well aligned with the gradient extrema, indicating that the uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 63 publications
2
54
0
Order By: Relevance
“…Using the values observed in +E hemisphere (the top row of columns 2 and 3 in the bottom part of Table ) and those observed in −E hemisphere (the top row of columns 4 and 5 in the bottom part of Table ), median (mean) escape rate of total O is calculated as 2.1 × 10 24 s (4.3 × 10 24 s). Suppose heavy ion outflows in the ion composition boundary are constant in all region, the area of the tail cross section becomes about 4 times larger around x MSO = −1.5 R M in comparison to that of the optical wake region (e.g., Xu et al, ), resulting in 4 times larger escape rate of total O, 8.3 × 10 24 s (1.7 × 10 25 s). Dong et al () showed that although the contributions of polar plumes to total heavy ion outflows change depending on solar EUV, several tens of percent of total heavy ion escapes are plume escape.…”
Section: Discussionmentioning
confidence: 99%
“…Using the values observed in +E hemisphere (the top row of columns 2 and 3 in the bottom part of Table ) and those observed in −E hemisphere (the top row of columns 4 and 5 in the bottom part of Table ), median (mean) escape rate of total O is calculated as 2.1 × 10 24 s (4.3 × 10 24 s). Suppose heavy ion outflows in the ion composition boundary are constant in all region, the area of the tail cross section becomes about 4 times larger around x MSO = −1.5 R M in comparison to that of the optical wake region (e.g., Xu et al, ), resulting in 4 times larger escape rate of total O, 8.3 × 10 24 s (1.7 × 10 25 s). Dong et al () showed that although the contributions of polar plumes to total heavy ion outflows change depending on solar EUV, several tens of percent of total heavy ion escapes are plume escape.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al () used a Block‐Adaptive Tree Solar wind Roe‐type Upwind Scheme Mars Multifluid magnetohydrodynamic model to study the three‐dimensional shape and structure of the pressure boundaries and the ICB. They found that the thickness of the boundaries are 0.05–0.1 R M (170–340 km) near the subsolar region and 1–1.5 R M (3,396–5,094 km) in the magnetotail.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the process of the IMB formation is governed by the solar wind and that the solar wind/ionosphere interface only occasionally could be described with the previously stated definition of the MPB. Xu et al (2016) used a Block-Adaptive Tree Solar wind Roe-type Upwind Scheme Mars Multifluid magnetohydrodynamic model to study the three-dimensional shape and structure of the pressure boundaries and the ICB. They found that the thickness of the boundaries are 0.05-0.1 R M (170-340 km) near the subsolar region and 1-1.5 R M (3,396-5,094 km) in the magnetotail.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Xu et al . [] examined output from a multifluid MHD simulation of the Mars space environment and found a tail current sheet shift to the + Y direction. On the other hand, the multifluid simulation results presented and discussed in Najib et al .…”
Section: Introductionmentioning
confidence: 99%